Предмет:
МатематикаАвтор:
аноним1) а + 2/4 + 3 * а - 1/3 + а - 2/2 = (1 + 3 + 1) * а + 1/2 - 1/3 - 1 = 5 * а + 3/6 - 2/6 - 6/6 = 5 * а + (3 - 2 - 6)/6 = 5 * а - 5/6 = 5 * (а - 1/6);
При а = -2:
5 * (а - 1/6) = 5 * (-2 - 1/6) = 5 * (-12/6 - 1/6) = 5 * (-13/6) = -65/6;
Ответ: -65/6.
2) 2 * b + 3/4 + b - 1/2 + 3/4 = (2 + 1) * b + 2 * 3/4 - 2/4 = 3 * b + 6/4 - 2/4 = 3 * b + 4/4 = 3 * b + 1;
При b = -3:
3 * b + 1 = 3 * (-3) + 1 = -9 + 1 = -8;
Ответ: -8.
3) 4 * а - 1/3 - 2 * а + 3/6 - 1/6 = (4 - 2) * а - 2/6 + 3/6 - 1/6 = 2 * а + 3/6 - 3/6 = 2 * а;
При а = 5:
2 * а = 2 * 5 = 10;
Ответ: 10.
Автор:
heathae9kДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Помогите решить тест очень надо(((Заранее спасибо
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть